A Unified Framework for Both Graph and Pattern Matching Using IPaMWAG (International Journal of Engineering and Computer Science, 2017)
In general the matter of finding sub graphs that best match a user’s query on weighted Attributed Graphs (wags) is an open research area. There is a tendency to outline a WAG as a graph where every nodes exhibit multiple attributes with varied, non-negative weights. An example of a WAG could be a coauthor ship network, wherever every author has multiple attributes, every such as a specific topic (e.g., databases, data processing, and machine learning), and therefore the quantity of experience in a very specific topic is delineate by a non-negative weight on it attribute. A typical user query during this setting specifies each property patterns between query nodes and constraints on attribute weights of the query nodes. A ranking perform that unifies the matching on attribute weights over the nodes and on the graph structure is proposed. To prove that the matter of retrieving the best match for such queries is complete. Moreover, there is a tendency to propose a quick and effective top-k pattern matching algorithm and top-k graph search algorithm for weighted attributed graphs. In an intensive experimental study with multiple realworld datasets, the projected algorithm exhibits important speed-up over competitive approaches. On average, projected technique is quicker in query process than the strongest competitive technique.